Malnutrition management in oncology: An expert view on controversial issues and future perspectives - Bossi, Paolo; De Luca, Raffaele; Ciani, Oriana; D’Angelo, Elisa; Caccialanza, Riccardo (Frontiers in Oncology, 2022)
Despite the recognized need for adequate nutritional support in cancer patients, in daily clinical practice nutrition is still not considered one of the first aspects to be considered. Malnutrition negatively affects the clinical outcomes, treatment response, and overall survival of cancer patients. In this study, three of the most controversial issues related to malnutrition, which emerged during an Italian Consensus Conference, were addressed specifically for patients with head and neck, as well as gastrointestinal cancer. Timing of nutritional evaluation and intervention, extension of the Enhanced Recovery after Surgery (ERAS®) protocols, and cost-effectiveness of nutritional interventions have been considered. This study aimed to illustrate the state-of-the art of each issue, hypothesize future perspectives and actions to be taken, trying to suggest a new nutritional management model for cancer patients in Italy that overcomes the critical issues encountered. Of note, the timely diagnosis of nutritional issue appears to be essential to ensure the correct management of malnourished cancer patients as well as those who are at high risk of malnutrition. Standardized protocols, screening tests, and the inclusion of nutritional parameters in patient medical records would help to achieve good clinical outcomes. Finally, appropriate nutritional support is also associated with cost savings, and it seems necessary to promote its clinical and economic value to obtain improvements in both outcomes and management costs.